Risk factors for metastatic osteoarticular infections after a long follow-up of patients with Staphylococcus aureus bacteraemia. (November 2015) - Lalueza, A.; Morales-Cartagena, A.; Chaves, F.; San Juan, R.; Laureiro, J.; Lora-Tamayo, J.; López-Medrano, F.; Orellana, M.Á.; Aguado, J.M.
Abstract: We aimed to identify risk factors associated with the development of haematogenous metastatic osteoarticular infection (MOI) after an episode of Staphylococcus aureus bacteraemia (SAB). We followed 198 patients with SAB during a median of 68.9 months. Nine (4.54%) developed an MOI (median: 6.77 months) after SAB. Factors associated with MOI were the presence of joint prosthesis (hazard ratio 17.56; 95% CI 4.48–68.85) and osteoporosis (hazard ratio 8.46; 95% CI 1.9–37.57). MOI is a common complication after SAB and is related to high morbidity and mortality. Patients with previous osteoarticular disease are at the greatest risk of developing this complication.